SPK LOKASI PEMBANGUNAN PERUMAHAN DI KABUPATEN LOMBOK TENGAH DENGAN METODE AHP - Aryandhana, Lalu Bintang; Fadli, Sofiansyah; Ashari, Maulana (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2022)
Decision Support System (DSS) is a system that can help someone in making decisions and is also an approach to support decision making on a particular problem. One of the methods in the decision support system is the Analytical Hierarchy Process (AHP) method, which is a method for making scientific and rational decisions to provide solutions to multi-criteria and complex problems with various alternatives. In this research, the author tries to apply the AHP method to determine the location of new housing developments in Lombok Tengah District. The criteria used for consideration are land conditions, facilities, social and economic conditions, and land availability. The results of this study can prove that DSS with the AHP method is able to assist developers in determining the choice of new housing development locations in Lombok Tengah District.